The Effect of Estrogen, Progesterone, and Its Combination on The Expression of Brain-Derived Neurotrophic Factor Medula Spinalis in Regeneration Process of Peripheral Nerve - Mochamad Rizki Yulianto1 , Agus Turchan1 , Hari Basuki Notobroto2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The presence of modulation factors in the regeneration process of peripheral nerve cellsinfluenced by estrogen and progesterone. Peripheral nerve injury is a fairly common case of trauma. Brainderived neurotrophic factor (BDNF) is the most active group of neurotrophins in stimulating neurogenesis.Objectives: To proves the effect of estrogen and progesterone on the expression of BDNF on the spinal cordin peripheral nerve regeneration process. Methods: Laboratory experimental study with the completelyrandomized design. Total transitory nerve ischiadicus was performed on four groups of rats. Each groupreceived hormone therapy according to the group. Hormone therapy is administered every 3 days for28 days, and on the 29th day is termination, spinal cord sampling, and followed by BDNF expressionexamination by Immunohistochemistry method. Results: In the control group, BDNF expression of spinalcord neuron cells was 93.0±14.0. In the treatment group, BDNF expression was obtained after estrogentherapy was 77.25±19.19, progesterone was 84.5±20.61, and in a combination of estrogen and progesteronewas 77.75±16.54. After statistical tests, no significant differences were found between the treatment groups(p = 0.316). Conclusion: The administration of estrogen, progesterone, or a combination of both did notsignificantly increase BDNF expression when compared to the control group.